Analysis of Mathematical Problem Solving Ability of XI Class Vocational Students on Composition Function Material - Gunawan, Muhamad; Yuspriati, Devi Nurul (IKIP Siliwangi, 2024)
This study aims to find out how well vocational students solve mathematical problems based on the composition function material. Mathematical problem solving ability is an ability that must be mastered by students because this ability is the core of mathematics. The location of this research is at SMK TI Garuda Nusantara and the main object of research is class XI students totaling 32 people in one class. The author used a descriptive qualitative approach. Several test questions were used as data collection methods. of 32 students in one class. It can be said that only 9 people were able to complete the test questions and get a good rating on each indicator. The results show that the problem solving ability of students in class XI of SMK TI Garuda Nusantara is classified as sufficient or moderate. This is very clear from the fact that only 28% of students who achieved perfect scores in the good category. 56% were rated medium, and 16% were rated low. The acquisition of the highest indicator value is in problem solving ability, while the lowest indicator is in the indicator of understanding the problem, this is due to the lack of understanding of basic mathematical concepts in students. In order for students' problem-solving skills to improve, researchers suggest that further research should use learning models or media that can help students understand mathematical concepts.